Translation and postcoloniality in Ireland: the particular and peculiar relationship between Irish Gaelic and English - Freeland Thompson, Tok (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Translations in Ireland (between Irish Gaelic and English) take place in two very different scenarios. In the southern Republic, the Irish language is officially the first national language, but it is now spoken by a bare fraction of the population, and is steadily declining as a living language. Translations between Irish and English are supported by the Republic ’s government in various schemes, but are often viewed with suspicion by many of the Irish Gaelic speakers as yet another colonialist move. In the North (Northern Ireland), the long history of repression has made the language a rallying point for nationalists. It is in this political minefield and threatened linguistic zone that both writer and translator must operate. Creative hybridity is revealed not as free of political enmeshments, but rather the reverse: the creative vitality of this particular bilingual writing zone (of both author and translator) results precisely from its highly pressurized milieu. This article argues that translations are served by the reflexive postcolonial understanding of the role of the translator and translation, as well as the original text, within the larger socio-political context.